Profil Pengelolaan dan Biaya Obat Tidak Digunakan pada Mahasiswa Farmasi Universitas Sari Mulia Banjarmasin - Juliana Safitri Kamah; Melviani Melviani; Eirene E.M Gaghauna (Jurnal Farmasi & Sains Indonesia, 2022)
Introduction: Health care as a whole is based on spending on drugs. Use of drugs that are not optimal also arise which will cause losses or cost losses due to drugs that are unusedObjective: Find the management of drugs and cost of unused drugs for Pharmacy students at Sari Mulia University, Banjarmasin. Methods: Research method used a survey type. Sampling technique used purposive sampling method with a total sample of 81 respondents. Data were analyzed using Microsoft Excel program. Results: Drug management for pharmacy students, most students get drugs at pharmacies, have paid attention to drug labels or brochures when using drugs, store drugs in place protected from sunlight, and dispose of drugs when drugs have expired. Drug costs based on the highest therapeutic class, namely analgesic, antipyretic, and anti-inflammatory therapy classes, namely Rp. 182,501. Reason the drug was unused was because it was cured at a cost of Rp. 289,038,-. The method or plan managing unused drugs is plan dispose of them in the trash a cost of Rp. 302,843 of the total cost obtained is Rp. 646,695,-. Conclusion: Conclusion of study is most of the students get their drugs at pharmacies, have paid attention to drug labels or brochures when using drugs, store drugs in a place protected from sunlight, and dispose of drugs when the drug has expired. Cost of drugs that are unused in this study is Rp. 646,695,- . Keywords: Drug Management, Cost, and Drug Unused